Teachers’ Leadership Skills for Positive Learning Environment among Teachers and Students’ Learning Outcome - Yadav, Seema (JOURNAL OF INDIAN EDUCATION, 2024)
This article delves into the pivotal role of teachers as leaders in education, recognising their profound impact on student learning outcomes. The multifaceted leadership responsibilities extend beyond the classroom, encompassing support for fellow educators, advocacy for enhanced educational practices, and a commitment to personal and collective success. The study emphasises the creation of a positive school climate, and culture through teacher leadership, fostering teamwork and harmony. Teacher leadership is explored as a catalyst for innovation, contributing to a collective leadership approach within schools. Beyond traditional administrative roles, teachers are positioned as intellectual and critical learners, consistently seeking to refine their teaching methods. This study underscores the importance of teacher leaders in influencing educational policies, elevating teaching standards and championing innovative practices. The findings highlight the concept of collective leadership as a potent force positively impacting teachers’ abilities, classroom instruction and overall student achievement. Teacher leaders are portrayed not only as educators but as influential advocates shaping the future of learning. The study concludes by asserting the increasing significance of teacher leadership in the evolving educational landscape, emphasising its crucial role in shaping the future of education. The scope of the study extends to the broad impact of teacher leadership on educational practices, policies and the overall learning environment.